Modulating the Substrate Stiffness to Manipulate Differentiation of Resident Liver Stem Cells and to Improve the Differentiation State of Hepatocytes. (12th January 2016) - Cozzolino, Angela Maria; Noce, Valeria; Battistelli, Cecilia; Marchetti, Alessandra; Grassi, Germana; Cicchini, Carla; Tripodi, Marco; Amicone, Laura
Abstract : In many cell types, several cellular processes, such as differentiation of stem/precursor cells, maintenance of differentiated phenotype, motility, adhesion, growth, and survival, strictly depend on the stiffness of extracellular matrix that, in vivo, characterizes their correspondent organ and tissue. In the liver, the stromal rigidity is essential to obtain the correct organ physiology whereas any alteration causes liver cell dysfunctions. The rigidity of the substrate is an element no longer negligible for the cultivation of several cell types, so that many data so far obtained, where cells have been cultured on plastic, could be revised. Regarding liver cells, standard culture conditions lead to the dedifferentiation of primary hepatocytes, transdifferentiation of stellate cells into myofibroblasts, and loss of fenestration of sinusoidal endothelium. Furthermore, standard cultivation of liver stem/precursor cells impedes an efficient execution of the epithelial/hepatocyte differentiation program, leading to the expansion of a cell population expressing only partially liver functions and products. Overcoming these limitations is mandatory for any approach of liver tissue engineering. Here we propose cell lines as in vitro models of liver stem cells and hepatocytes and an innovative culture method that takes into account the substrate stiffness to obtain, respectively, a rapid and efficient differentiation process and the maintenance of the fully differentiated phenotype.